Divisions of Labour: Skilled Workers and Technological Change in Nineteenth Century Britain - Finkel, Alvin (Labour / Le Travail, 1987)
This article reviews the book, "Divisions of Labour: Skilled Workers and Technological Change in Nineteenth Century Britain," by Royden Harrison & Jonathan Zeitlin, edited.
Keywords: DIVISIONS of Labour: Skilled Workers & Technological Change in Nineteenth-Century Britain (Book); Division of labor; HARRISON; Royden; Nonfiction; REVIEWS; ZEITLIN; Jonathan; books